DEBT ON ASSET RATIO, RETURN ON ASSET AND AUDIT OPINION TOWARD RETURN SHARE WITH THE INTERVENING AUDIT DELAY VARIABLE (STUDI IN MANUFACTURED COMPANY REGISTERED IN BEI IN 2015-2017) - Titik Dwiyani; Purnomo Purnomo; Darmanto Darmanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The aim of this research is to comprehend whether the DAR, ROA, Audit Opinion variable influenced the return share and whether the intervening audit delay variable is able to moderate the independent variable toward return share. The population and the research sample are 54 manufactured companies which are registered in BEI in 2015-2017. The analysis used is multiple linear regression and path analysis. The result of this research was the evidence that DAR, ROA, and Audit Opinion affected the return share. Meanwhile, path analysis using Audit Delay as intervening variable only moderated the audit opinion variable toward return share. But Audit Delay was not able to moderate DAR, ROA variable toward return share. Keywords: DAR, ROA, Audit Opinion, Audit delay and Return share.